Dep??sitos a prazo com garantia especial e o risco moral: evid??ncias nos bancos brasileiros - Androvandi, Gilberto Hanssen (2017)
This paper investigates evidences of moral hazard in small and medium-sized Brazilian banks (SMB) that issued Time Deposits with Special Deposit Guarantee (DPGE), this product was created in 2008 Crisis, addressed to wholesale or institutional investors, and coverage by deposit insurance from Credit Guarantee Fund (FGC). For this purpose, we will use a differences-in-differences estimator (DID), comparing the results between DPGE issuers (treatment group) and DPGE nonissuers (control group) considering two banking risk measures (NPL and Basel Index) Data Collection comprehends information between June 2007 and December 2015 grouped in a panel data with significant events in the Brazilian banking market such as impact of global crisis of 2007-2008, the domestic securitization crisis and idiosyncratic events with potential contagion. Our evidence does not suggest the occurrence of moral hazard associated with the set of banks that emit DPGE. The result is in line with recent literature findings suggesting that there is not necessarily increased risk-taking by banks with the introduction of deposit insurance guarantees, provided that it is supported by an adequate design of the deposit insurance scheme by policymakers.